SISTEM AIR BERSIH DI DESA BELOK SIDAN MENERAPKAN METODE POMPA AIR DENGAN PENGGERAK KINCIR AIR - Tenaya, I.G.N.P.; Sukadana, I.G.K.; Mataram, K. (Buletin Udayana Mengabdi; Vol 16 No 3 (2017), 2018)
Jempanang hamlet located in the district of Badung regency evening. The population of the hamlet Jempanang are 150 families (750 people), 95% of the population work as farmers and ranchers. To meet the demand for water Jempanang Hamlet residents currently take away from the water source Pucak Kangin who has a discharge of 10 liters per second, which is only used 10 percent. And the position of water sources Pucak Kangin with Jempanang hamlet of about 1500 m. So the water that reached the hamlet Jempanang not sufficient to meet the needs of the whole community Jempanang. People who are in the higher residential areas untouched by water. In the village there is also a water source Jempanang Puseh Kangin were big enough, but because the position is very far down from the position of the population, these water sources until now have not in use. Therefore, people had the idea to utilize water resources Puseh Kangin, but obstacles in the application of appropriate technology. From the initial survey and mapping of the situation it was decided to apply the technology of piston pumps are driven by a waterwheel. From the testing / evaluation is carried out at an altitude of 120 m from the pumping station pumping discharge obtained for 0.014 liters / sec. If the pump runs 24 hours, the volume of water pumped as much as 1200 liters a day. The water needs of the rural population an average of 60 liters / person / day, so new enough for 20 people (5 families). But if it is only used for consumption purposes drinking and cooking then enough for 120 people (25 families). So it can solve the problem of drinking water 20 families residing in the Puncak area.